Perceptions of parents and paediatricians on pain induced by bone marrow aspiration and lumbar puncture among children with acute leukaemia: a qualitative study in China. Issue 9 (21st September 2017) - Wang, Yu; Liu, Qiang; Yu, Jia-Ning; Wang, Hai-Xia; Gao, Lu-Lu; Dai, Ya-Liang; Jin, Xin; Zuo, Feng; Liu, Juan; Bai, Cai-Feng; Mu, Guo-Xia; Chai, Xiao-Min; et al.
Abstract : Objective: To obtain in-depth insight into the perceptions of parents and paediatricians in China regarding current procedural pain management on bone marrow aspirations and lumbar punctures in paediatric haemato-oncology department. Design, setting and participants: This qualitative study was conducted in a 4500-bed university hospital in northwest China. To collect data, in-depth semistructured interviews were conducted with parents of children with acute leukaemia (n=12) and haemato-oncology paediatricians (n=11) using purposive sampling. Interviews were audiotaped and transcribed and subjected to thematic analysis. Results: The suffering of procedural pain among paediatric patients was not adequately recognised and properly treated at the paediatric haemato-oncology department. The current paediatric procedural pain management is inadequate for paediatric patients. Crucial factors were identified including lack of awareness about the damage of uncontrolled pain in children, parents' low supportive ability, the limited capacity to provide general analgesia by anaesthetists, inadequate knowledge in the usage of analgesia and sedation and lack of efficient analgesic for children's procedural pain. The participants strongly expected optimal interventions to improve paediatric procedural pain management. Conclusions: The result suggested a perceived and actual poor management of paediatric procedural pain in haemato-oncology department in northwest China. A relevant pain management education programme for paediatricians and parents as well as an effective pain medication are urgently needed in northwest China. Trial registration: Chinese Clinical Trial Registry. Identifier: ChiCTR-INR-16007989.